Observation of modes in the sub-cyclotronic range of frequencies in JET - F. Nabais; D. Borba; R. Coelho; J. Ferreira; A. Figueiredo; P. Rodrigues; S.E. Sharapov; JET Contributors (Nuclear Fusion, 2024)
The excitation of modes in the JET tokamak in the sub-cyclotronic range of frequencies (frequencies comprised between the Alfvén frequency and the cyclotron frequency) is for the first time reported. The modes were identified as compressional Alfvén eigenmodes and have characteristics similar to those of the sub-cyclotronic modes observed in other tokamaks, in particular those first reported in the NSTX tokamak. On the other hand, the modes observed in JET present some unique features and were observed to be excited by ion cyclotron resonance heating instead of by the injection of beams (neutral beam injection).